2013
DOI: 10.1016/j.jbiomech.2012.11.039
|View full text |Cite
|
Sign up to set email alerts
|

Bone fragility beyond strength and mineral density: Raman spectroscopy predicts femoral fracture toughness in a murine model of rheumatoid arthritis

Abstract: Clinical prediction of bone fracture risk primarily relies on measures of bone mineral density (BMD). BMD is strongly correlated with bone strength, but strength is independent of fracture toughness, which refers to the bone’s resistance to crack initiation and propagation. In that sense, fracture toughness is more relevant to assessing fragility-related fracture risk, independent of trauma. We hypothesized that bone biochemistry, determined by Raman spectroscopy, predicts bone fracture toughness better than B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
44
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 61 publications
(80 reference statements)
4
44
0
Order By: Relevance
“…Blind decomposition methods, 55,56 if properly constrained, could also potentially be used to estimate bone spectra based on transcutaneous measurements. The results of this study demonstrate that the mineral/matrix ratio of cortical bone, which has frequently been used as a Raman-based indicator of bone health and strength, [4][5][6][7][8][9][10][11][12][13][14] can be measured transcutaneously by processing SORS data sets with SOLD ( Figs. 10 and 11).…”
Section: Methodsmentioning
confidence: 74%
See 2 more Smart Citations
“…Blind decomposition methods, 55,56 if properly constrained, could also potentially be used to estimate bone spectra based on transcutaneous measurements. The results of this study demonstrate that the mineral/matrix ratio of cortical bone, which has frequently been used as a Raman-based indicator of bone health and strength, [4][5][6][7][8][9][10][11][12][13][14] can be measured transcutaneously by processing SORS data sets with SOLD ( Figs. 10 and 11).…”
Section: Methodsmentioning
confidence: 74%
“…2 Vibrational spectroscopy has been used extensively in ex vivo studies to measure the chemical composition of both the mineral and organic matrix components of bone. 3,4 Specifically, Raman spectroscopy has revealed chemical perturbations to cortical bone in animal studies of aging, 5 lead exposure, 6 osteogenesis imperfecta, 7 early-onset osteoarthritis, 8 rheumatoid arthritis, 9 and glucocorticoid-induced osteoporosis 10,11 and in a study of women with postmenopausal osteoporosis. 12 Many studies have also revealed correlations between Raman spectroscopy-based measures of chemical composition and the biomechanical properties of bone.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…32 Although each would require significant empirical support to extend mechanistically to analysis of turbid bone tissue, unsupervised multivariate analysis allows for the influence of these known RS sensitivities to be related to mechanical outcomes without spurious mechanistic suppositions. Indeed, recent applications of multivariate RS analyses to bone have helped explain the fracture toughness of bone in a model of rheumatoid arthritis 33 as well as partial mechanical improvement of OI mouse bones after human stem cell transplant. 34 Therefore, we investigated the potential of full spectrum multivariate analysis with a "bottom-up" design built upon the principal directions of Raman variance between test groups.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, optical coherence tomography (OCT) can measure depth-resolved tissue morphology up to one millimeter below the tissue surface [3,4] depending upon the type of tissue and its associated optical properties. Chemically-sensitive optical methods, such as Raman spectroscopy (RS) [5][6][7][8][9][10][11], can measure spatiotemporal distributions of analytes with up to micron-level spatial resolution when utilizing confocal detection [12]. In fact, confocal Raman spectroscopy has been recently applied, using commercially-available instrumentation, to detect Tenofovir in tissue samples ex vivo [13].…”
Section: Introductionmentioning
confidence: 99%